Characteristics and Experiences of Parents of Children with Learning and Attention Disabilities and Autism Spectrum Disorder: A Mixed Methods Study. (July 2022) - Chad-Friedman, Emma; Kuhlthau, Karen A.; Millstein, Rachel A.; Perez, Giselle K.; Luberto, Christina M.; Traeger, Lara; Proszynski, Jacqueline; Park, Elyse
Parents of children with learning and attention disorders (LAD) and autism spectrum disorder (ASD) experience chronic parenting stress due to the challenges in raising a child with special needs. We used a mixed methods design to examine characteristics and experiences of stress and coping among parents of children with LAD and ASD. We conducted 20 semi-structured focus group interviews with parents of children with LAD ( n  = 11) and ASD ( n  = 9) and administered a battery of self-report measures of stress and coping to parents of LAD ( n  = 53) and ASD ( n  = 51) enrolled in a pilot trial. Qualitative findings showed that parents of children with LAD and ASD largely experienced similar sources of stress, but with different intensities due to their children's different difficulties. Quantitative findings reflected high levels of distress among parents of children with LAD and ASD, with parents of children with ASD demonstrating higher distress and poorer overall sleep quality. Stressors experienced by parents of children with ASD arose from more overt challenges associated with having a child with more visible challenges. Parents of children with LAD experienced more subtle challenges of having a child who is less overtly impaired. Findings will aid in the development of targeted stress management interventions.